Improving Biographical Text Writing Skills Using Paired Models and Process Differentiation Approaches at X-7 SMA Negeri 21 Surabaya - Ayu Familia Nur Janah, Intan; Kaswadi; Isma Sholihah (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
Abstract This research aims to improve the biographical text writing skills of class X-7 students at SMA Negeri 21 Surabaya using the Think Pair Share cooperative model with a process differentiation approach. This research uses the Classroom Action Research (CAR) method with 4 stages: planning, action, observation and reflection. The research results show that the Think Pair Share cooperative model with a process differentiation approach can improve students' ability to write biographical texts. This is proven by the increase in scores and observation results from cycle I to cycle II. In cycle I, the lowest value was 75 and the highest was 96 with an average increase of 16%. In cycle II, the lowest value was 80 and the highest was 98 with an average increase of 23%. The observation results for cycle I were 85% and cycle II were 92%. The conclusion of this research is that the Think Pair Share cooperative model with a process differentiation approach is effective for improving the biographical text writing skills of class X-7 students at SMA Negeri 21 Surabaya.